High-hardness, wear-resistant member and manufacturing method thereof
A high-hardness, wear-resistant member with a Ni-Fe matrix and oriented WC crystal particles, manufactured via electroless plating and gas carburizing, addresses the strength-toughness trade-off and brittle phase issues, achieving superior wear resistance and adhesion.
Patent Information
- Application Number
- JP2020187486
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-10
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-11-10
AI Technical Summary
Existing high-speed tool steels face a trade-off between strength and toughness, and surface coatings like cermet materials with tungsten carbide (WC) and Co binder form brittle phases, compromising wear resistance and adhesion.
A high-hardness, wear-resistant member with a base material and coating structure, where the coating comprises a matrix of Ni-Fe solid solution and a hard layer of WC crystal particles, with specific size and orientation, and is manufactured through electroless plating, W single-phase crystal formation, and gas carburizing processes.
The solution provides a member with high hardness, excellent wear resistance, and strong adhesion between the base material and coating, enhancing durability and reliability.
Smart Images

Figure 0007604736000004 
Figure 0007604736000005 
Figure 0007604736000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-hardness, wear-resistant member and a method for producing the same. [Background technology]
[0002] High-speed tool steels have been used as cutting tool and die materials for some time. High strength and toughness are required for high-speed tool steels, as they are directly related to the wear resistance and lifespan of the above-mentioned applications.
[0003] However, since there is generally a trade-off between strength and toughness, materials and manufacturing conditions have been adjusted taking into account the balance between strength and toughness depending on the application and cost.
[0004] For example, Patent Document 1 proposes a high-speed tool steel with improved toughness by appropriately controlling the heat treatment conditions for a low-alloy high-speed tool steel.
[0005] Moreover, Patent Document 2 proposes a method of reducing the amount of expensive additive elements added while ensuring strength by devising additive chemical components.
[0006] In order to reduce costs and ensure ease of molding and processing, a technique is also known in which a hard coating is formed on the surface of a widely available steel material or the like used as a substrate. One such method is a method (high-velocity flame spraying) in which a material (cermet material) containing tungsten carbide (WC) particles and Co as a binder is sprayed to form a coating. However, this method has the problem that a brittle phase is formed due to the reaction between WC and Co. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2004-307963 A [Patent Document 2] JP 2014-145100 A Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a high-hardness, wear-resistant member that has high hardness and excellent wear resistance as well as excellent adhesion between the substrate and a hard coating, and to provide a method for producing said high-hardness, wear-resistant member. [Means for solving the problem]
[0009] Such objectives are as follows: 13 This is achieved by the present invention described in (1) A high-hardness, wear-resistant member having a substrate and a coating, The coating has a matrix made of a material containing a solid solution containing Ni and Fe, and a hard layer made of a material containing WC crystal grains and supported by the matrix. the law of nature, The mother phase is provided in a layer shape between the substrate and the hard layer, The WC crystal grains have a minor axis length of 0.10 μm or more and 1.4 μm or less and a major axis length of 1.0 μm or more and 4.0 μm or less. A high-hardness, wear-resistant member characterized by:
[0010] (2) The high hardness and wear-resistant member according to the above (1), wherein the hard layer has a thickness of 0.5 μm or more.
[0011] (3) The high hardness and wear-resistant member according to (1) or (2) above, wherein the substrate is made of a steel material.
[0012] (4) The high-hardness, wear-resistant member according to the above (3), wherein the substrate is made of carbon steel.
[0013] (5) A high-hardness, wear-resistant member according to any one of (1) to (4) above, wherein the coating has a thickness of 1.5 μm or more and 5.0 μm or less.
[0014] (6) A high-hardness, wear-resistant member according to any one of (1) to (5) above, wherein the hard layer contains rod-shaped WC crystal grains.
[0016] ( 7 ) an electroless plating process in which electroless Ni-P plating is applied to a base material made of a material containing Fe to form an electroless Ni-P plating layer; an electroplating step of forming a Ni-W alloy plating layer on the electroless Ni-P plating layer by electroplating; a W single-phase crystal forming step of forming a composite layer containing W single-phase crystals and a solid solution containing Ni and Fe by performing a heat treatment in a reducing atmosphere; and a carburizing step of forming WC crystal particles by subjecting the composite layer to a gas carburizing treatment.
[0017] ( 8 The thickness of the electroless Ni-P plating layer formed in the electroless plating step is 0.01 μm or more and 10 μm or less. 7 ) A method for producing a high hardness, wear-resistant member according to the present invention.
[0018] ( 9 The thickness of the Ni-W alloy plating layer formed in the electroplating step is 1.0 μm or more and 10 μm or less. 7 )or( 8 ) A method for producing a high hardness, wear-resistant member according to the present invention.
[0019] ( 10 The W single-phase crystal formation step is carried out by carrying out a heat treatment at 500° C. or more and 1000° C. or less in a reducing atmosphere. 7 ) or ( 9 2. A method for producing a high hardness, wear-resistant member according to any one of claims 1 to 11.
[0020] ( 11 The W single-phase crystal formation step is carried out by carrying out a heat treatment for 10 minutes to 180 minutes in a reducing atmosphere. 7 ) or ( 102. A method for producing a high hardness, wear-resistant member according to any one of claims 1 to 11.
[0021] ( 12 The carburizing step is carried out by carrying out a heat treatment at 650°C to 1000°C in an atmosphere containing a carburizing gas. 7 ) or ( 11 2. A method for producing a high hardness, wear-resistant member according to any one of claims 1 to 11.
[0022] ( 13 The carburizing step is carried out by carrying out a heat treatment for 3 minutes or more and 180 minutes or less in an atmosphere containing a carburizing gas. 7 ) or ( 12 2. A method for producing a high hardness, wear-resistant member according to any one of claims 1 to 11. Effect of the Invention
[0023] According to the present invention, it is possible to provide a high-hardness, wear-resistant member that has high hardness and excellent wear resistance as well as excellent adhesion between the substrate and the hard coating, and to provide a method for producing the high-hardness, wear-resistant member. [Brief description of the drawings]
[0024] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a preferred embodiment of the high-hardness, wear-resistant member of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a preferred embodiment of the method for producing a high-hardness, wear-resistant member of the present invention. [Diagram 3] FIG. 3 is a diagram showing X-ray diffraction (XRD) patterns at the end of the W single-phase crystal formation step and at the end of the carburization treatment step for Examples 1 and 2. [Figure 4] FIG. 4 is a diagram showing X-ray diffraction (XRD) patterns for Examples 3 and 4 at the end of the carburization treatment process. [Diagram 5] FIG. 5 is a diagram showing X-ray diffraction (XRD) patterns of Comparative Examples 1 and 2 at the end of the carburization treatment process. [Figure 6]FIG. 6 is a surface SEM (scanning electron microscope) photograph of the high-hardness, wear-resistant members of Examples 1 and 2. [Figure 7] FIG. 7 is a SEM (scanning electron microscope) photograph of the surface of the high-hardness, wear-resistant members of Comparative Examples 1 and 2. [Figure 8] FIG. 8 is a diagram showing the results of cross-sectional energy dispersive X-ray analysis (EDS) at the end of the W single-phase crystal formation process for Example 3. [Figure 9] FIG. 9 shows the results of surface energy dispersive X-ray analysis (EDS) at the end of the carburization treatment process for Example 3. [Figure 10] FIG. 10 is a diagram showing the results of surface electron backscatter diffraction (EBSD) at the end of the carburization treatment process for Example 3. [Figure 11] FIG. 11 is a diagram showing the results of cross-sectional energy dispersive X-ray analysis (EDS) at the end of the carburization treatment process for Example 3. [Figure 12] FIG. 12 is a diagram showing the results of surface energy dispersive X-ray analysis (EDS) at the end of the carburization treatment process for Example 4. [Figure 13] FIG. 13 is a diagram showing the results of surface EDS / EBSD at the end of the carburization treatment process for Example 4. [Figure 14] FIG. 14 is a diagram showing the results of cross-sectional energy dispersive X-ray analysis (EDS) at the end of the carburization treatment process for Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Preferred embodiments of the present invention will now be described in detail. [1] High hardness and wear-resistant parts First, the high hardness and wear resistant member of the present invention will be described. FIG. 1 is a schematic cross-sectional view showing a preferred embodiment of the high-hardness, wear-resistant member of the present invention.
[0026] 1, the hardness and wear-resistant member 100 has a substrate 1 and a coating 2. The coating 2 has a matrix 21 made of a material containing a solid solution containing Ni and Fe, and a hard layer 22 made of a material containing WC crystal grains.
[0027] With this configuration, it is possible to provide a high-hardness, wear-resistant member 100 that has high hardness and excellent wear resistance, and also has excellent adhesion between the substrate and the hard coating.
[0028] [1-1] Base material The substrate 1 has a function of supporting the coating 2 , and usually constitutes the main portion of the high-hardness, wear-resistant member 100 .
[0029] Moreover, the substrate 1 usually has the same general shape as the entire hardness and wear-resistant member 100 .
[0030] The substrate 1 may be made of any material. Examples of the material for the substrate 1 include various metal materials, various ceramic materials, various glass materials, various resin materials, stone materials, and carbon materials, and preferably contains at least Fe.
[0031] This allows Fe to be suitably contained in the matrix 21 without forming a film containing Fe by various film-forming methods when manufacturing the hardness and wear-resistant member 100. In particular, the matrix 21 containing Fe can be suitably formed by using a method to be described later. Also, the adhesion between the substrate 1 and the matrix 21 can be made particularly excellent.
[0032] Among them, it is preferable that the substrate 1 is made of a steel material. This can increase the hardness of the high hardness and wear-resistant member 100 as a whole. It also improves the adhesion between the substrate 1 and the coating 2. Furthermore, steel is relatively inexpensive and easily available, and is therefore preferable from the standpoint of stable supply of the high hardness and wear-resistant member 100 and reduction in manufacturing costs.
[0033] Examples of the steel material constituting the substrate 1 include carbon steel, stainless steel, and alloy steel such as manganese steel.
[0034] In particular, the substrate 1 is preferably made of carbon steel. This can improve the workability of the substrate 1, making it suitable for use in the manufacture of high-hardness, wear-resistant members 100 of various shapes. It can also improve the adhesion between the substrate 1 and the coating 2. Carbon steel is particularly inexpensive and easily available among various steel materials, and is therefore particularly preferred from the viewpoints of stable supply of the high-hardness, wear-resistant members 100 and reduction in manufacturing costs.
[0035] Examples of carbon steel constituting the substrate 1 include low carbon steel having a carbon content of 0.02% by mass or more and 0.25% by mass or less, medium carbon steel having a carbon content of 0.25% by mass or more and 0.6% by mass or less, and high carbon steel having a carbon content of 0.6% by mass or more.
[0036] The substrate 1 may be, for example, entirely made of a uniform material, or may have a plurality of regions made of different materials. For example, the substrate 1 may have a base and a surface layer that covers at least a portion of the base. At least one intermediate layer may be provided between the base and the surface layer.
[0037] The shape of the substrate 1 is not particularly limited, but is usually similar to the general shape of the high-hardness, wear-resistant member 100 .
[0038] The substrate 1 may have regions with different compositions. For example, the substrate 1 may have a base and a surface layer with a different composition from the base, may be a laminate having multiple layers, or may be made of a gradient material in which the composition of the constituent materials changes in a gradient manner. In such cases, it is preferable that at least the surface of the substrate 1 is made of the material described above.
[0039] [1-2]Coating The hard and wear-resistant component 100 has a coating 2 supported on a substrate 1 . The coating 2 has a matrix 21 made of a material containing a solid solution containing Ni and Fe, and a hard layer 22 made of a material containing WC crystal grains.
[0040] The coating 2 mainly has the function of increasing the hardness of the high-hardness, wear-resistant member 100 and improving the wear resistance of the high-hardness, wear-resistant member 100 .
[0041] [1-2-1]Matrix The parent phase 21 is composed of a material including a solid solution containing Ni and Fe. Such a parent phase 21 is usually provided in a portion in contact with the substrate 1 and the hard layer 22 .
[0042] Since the parent phase 21 is composed of the above-mentioned material, the adhesion of the parent phase 21 to the substrate 1 and the adhesion of the parent phase 21 to the hard layer 22 can both be excellent.
[0043] The solid solution constituting the parent phase 21 may contain Ni and Fe, but may also contain W.
[0044] This can improve the hardness and wear resistance of the entire hardness and wear-resistant member 100. Also, the adhesion of the parent phase 21 to the hard layer 22 can be improved.
[0045] The solid solution constituting the parent phase 21 may contain components other than those mentioned above. However, the content of components other than Ni, Fe, and W in the solid solution constituting the parent phase 21 is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 1 mass % or less.
[0046] Furthermore, the parent phase 21 may contain other components in addition to the solid solution. However, the proportion of components other than the solid solution in the parent phase 21 is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 1 mass % or less.
[0047] The parent phase 21 may have any shape, but is usually provided in the form of a layer between the substrate 1 and the hard layer 22 .
[0048] In such a case, the thickness of the parent phase 21 is not particularly limited, but is preferably 1.0 μm or more and 2.5 μm or less, and more preferably 1.0 μm or more and 2.0 μm or less.
[0049] This makes it possible to improve the balance between the hardness and abrasion resistance of the high hardness and abrasion-resistant member 100 and the adhesion between the substrate 1 and the coating 2. In addition, the productivity of the high hardness and abrasion-resistant member 100 can be improved.
[0050] The parent phase 21 may be, for example, entirely made of a uniform material, or may have a plurality of regions made of different materials.
[0051] [1-2-2] Hard layer The coating 2 is made of a material containing WC crystal grains, and has a hard layer 22 supported by a matrix 21 .
[0052] Such a hard layer 22 has extremely high hardness and excellent wear resistance, and further has excellent adhesion to the parent phase 21. This makes it possible to provide the high-hardness, wear-resistant member 100 as a whole with excellent hardness and wear resistance. Furthermore, unintended peeling of the coating 2 and the like is effectively prevented, and the high-hardness, wear-resistant member 100 can be provided with excellent durability and reliability.
[0053] The WC crystal grains contained in the hard layer 22 may be of any shape, but it is preferable that the hard layer 22 contains rod-shaped WC crystal grains, and it is even more preferable that these are selectively oriented in the thickness direction of the coating 2.
[0054] This more effectively prevents the WC crystal particles from falling off the surface of the hard layer 22 during friction, wear, and sliding with other objects, and further improves the wear resistance.
[0055] The WC crystal grains are not particularly limited, but preferably have a minor axis length of 0.10 μm or more and 1.4 μm or less and a major axis length of 1.0 μm or more and 4.0 μm or less, more preferably have a minor axis length of 0.30 μm or more and 1.20 μm or less and a major axis length of 1.5 μm or more and 3.5 μm or less, and even more preferably have a minor axis length of 0.50 μm or more and 1.00 μm or less and a major axis length of 2.0 μm or more and 3.0 μm or less.
[0056] As a result, in a state where the above-mentioned selective orientation in the thickness direction of the coating 2 is achieved, the thickness of the hard layer 22 and the major axis length of the WC crystal grains match each other.
[0057] In this specification, the crystal grains to be measured on the surface of the portion to be measured (for example, the hard layer 22 for WC crystal grains) are detected using image analysis software, and the short axis length and long axis length of all of the crystal grains are determined, and the arithmetic mean values of each are defined as the short axis length and long axis length of the crystal grain.
[0058] The hard layer 22 is made of a material containing WC crystal grains, but may further contain components other than WC.
[0059] However, the content of components other than WC in the hard layer 22 is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 1 mass % or less.
[0060] The thickness of the hard layer 22 is not particularly limited, but is preferably 0.5 μm or more, and more preferably 1.0 μm or more and 2.5 μm or less.
[0061] This makes it possible to improve the balance between the hardness and abrasion resistance of the high hardness and abrasion-resistant member 100 and the adhesion between the substrate 1 and the coating 2. In addition, the productivity of the high hardness and abrasion-resistant member 100 can be improved.
[0062] The hard layer 22 may be, for example, entirely made of a uniform material, or may have a plurality of regions made of different materials.
[0063] In the illustrated configuration, a clear boundary exists between the layered parent phase 21 and the hard layer 22, but the boundary between the parent phase 21 and the hard layer 22 may be unclear, and may have, for example, a region in which the constituent material of the parent phase 21 and the constituent material of the hard layer 22 are mixed. The coating 2 may have a region other than the parent phase 21 and the hard layer 22, such as an intermediate layer or a base layer. Examples of such a region include a region that contains Ni but does not contain Fe.
[0064] Furthermore, in the illustrated configuration, there is a clear boundary between the substrate 1 and the coating 2, but the boundary between the substrate 1 and the coating 2 may be unclear.
[0065] The thickness of the coating 2 is not particularly limited, but is preferably 1.5 μm or more and 5.0 μm or less, and more preferably 2.0 μm or more and 4.5 μm or less.
[0066] This makes it possible to improve the balance between the hardness and abrasion resistance of the high hardness and abrasion-resistant member 100 and the adhesion between the substrate 1 and the coating 2. In addition, the productivity of the high hardness and abrasion-resistant member 100 can be improved.
[0067] The coating 2 only needs to cover at least a part of the surface of the substrate 1 , and the substrate 1 may have a portion that is not covered with the coating 2 .
[0068] The hardness and wear-resistant member 100 may further have other components in addition to the above-mentioned substrate 1 and coating 2. Examples of such components include an intermediate layer provided between the substrate 1 and coating 2, and a coating layer that covers at least a portion of the surface of the coating 2. Furthermore, when the substrate 1 has an area that is not covered with the coating 2, that area may be covered with a film other than the coating 2.
[0069] As described above, the high-hardness, wear-resistant member 100 has high hardness and excellent wear resistance, and also has excellent adhesion between the substrate 1 and the coating 2 .
[0070] The Vickers hardness of the portion of the high hardness and wear-resistant member 100 where the coating 2 is provided, measured in accordance with the Vickers hardness testing method specified in JIS Z 2244, is preferably 1000 or more and 2700 or less, more preferably 1100 or more and 2500 or less, and even more preferably 1200 or more and 2300 or less.
[0071] The Vickers hardness can be determined, for example, by measurement using a microhardness tester (Fisher Instruments, Picodentor HM500).
[0072] The specific wear rate of the portion of the hardness and wear-resistant member 100 on which the coating 2 is formed is determined by a ball-on-disk friction and wear test specified in ISO 18535. -16 m 2 / N or less, and preferably 1.4×10 -16 m 2 / N or more 2.5×10 -16 m 2 It is more preferable that the ratio is equal to or less than 1 / N.
[0073] For the ball-on-disk friction and wear test, for example, a ball-on-disk friction and wear tester (Tribometer, manufactured by CSM Instruments) can be used.
[0074] The high hardness and wear-resistant member 100 may be used for any purpose, but is preferably used for purposes requiring high hardness and wear resistance, such as various tools such as cutting tools, various rolls such as metal molds and rolling rolls, various sliding parts such as piston rings, cylinders, bearings, and various valves and pump parts.
[0075] [2] Manufacturing method for high-hardness, wear-resistant parts Next, a method for producing the high hardness and wear resistant member of the present invention will be described. FIG. 2 is a schematic cross-sectional view showing a preferred embodiment of the method for producing a high-hardness, wear-resistant member of the present invention.
[0076] As shown in FIG. 2, the method for producing the hardness and wear-resistant member 100 of this embodiment includes a substrate preparation step (1a) of preparing a substrate 1 made of a material containing Fe, an electroless plating step (1b) of applying electroless Ni-P plating to the substrate 1 to form an electroless Ni-P plating layer 2A', an electroplating step (1c) of forming a Ni-W alloy plating layer 2B' on the electroless Ni-P plating layer 2A' by electroplating, a W single-phase crystal formation step (1d) of forming a composite layer 2' containing W single-phase crystals and a solid solution containing Ni and Fe by performing a heat treatment in a reducing atmosphere, and a carburization treatment step (1e) of forming WC crystal particles by performing a gas carburization treatment on the composite layer 2'.
[0077] This makes it possible to provide a method for producing a high-hardness, wear-resistant member 100 that has high hardness and excellent wear resistance, and also has excellent adhesion between the substrate 1 and the hard coating 2. In particular, the high-hardness, wear-resistant member 100 having the above-mentioned excellent properties can be produced with good productivity and excellent yield.
[0078] [2-1] Substrate preparation process In the substrate preparation step, the substrate 1 as described above, in particular the substrate 1 made of a material containing at least Fe, is prepared (1a).
[0079] The substrate 1 prepared in this step may be one that has been subjected to a cleaning treatment or a surface treatment such as mirror finishing, blasting, or plasma treatment.
[0080] [2-2] Electroless plating process In the electroless plating step, electroless Ni-P plating is applied to the base material 1 to form an electroless Ni-P plating layer 2A' (1b).
[0081] The electroless plating step can be suitably carried out by using a plating solution having a Ni concentration of 3 g / L or more and 10 g / L or less.
[0082] As the plating solution, for example, a commercially available plating solution may be used as it is, or a commercially available plating solution raw material may be used which has been prepared by diluting or the like.
[0083] The pH (pH at 25° C.) of the plating solution used in the electroless plating step is not particularly limited, but is preferably 3.0 or more and 4.5 or less, and more preferably 3.3 or more and 4.2 or less.
[0084] The treatment temperature in the electroless plating step is not particularly limited, but is preferably 50°C or higher and 95°C or lower, and more preferably 60°C or higher and 90°C or lower.
[0085] The processing conditions in the electroless plating step (eg, processing temperature, etc.) may be changed during the electroless plating step.
[0086] The treatment time of the electroless plating step is not particularly limited, but is preferably from 10 minutes to 120 minutes, and more preferably from 15 minutes to 60 minutes.
[0087] This can improve the reliability of the finally obtained high hardness and wear resistant member 100. Also, the productivity of the high hardness and wear resistant member 100 can be improved.
[0088] The thickness of the electroless Ni-P plating layer 2A' formed in the electroless plating process is not particularly limited, but is preferably 0.01 μm or more and 10 μm or less, more preferably 0.1 μm or more and 5.0 μm or less, and even more preferably 1.5 μm or more and 2.0 μm or less.
[0089] This makes it possible to suitably adjust the thickness of the coating 2 and the thickness of the parent phase 21 in the finally obtained high hardness and wear-resistant component 100 so as to satisfy the above-mentioned conditions.
[0090] [2-3] Electroplating process In the electroplating step, a Ni--W alloy plating layer 2B' is formed on the electroless Ni--P plating layer 2A' by electroplating (1c).
[0091] The Ni—W alloy plating layer 2 B′ is a constituent component of the parent phase 21 and also serves as a W source for the WC that constitutes the hard layer 22 .
[0092] The electroplating step can be suitably carried out by using, for example, a plating solution containing tungstate ions, nickel ions and a complexing agent therefor.
[0093] The tungstate ions are preferably contained in the plating solution in the form of a highly water-soluble salt such as sodium tungstate, potassium tungstate, or ammonium tungstate.
[0094] The nickel ions are preferably contained in the plating solution in the form of a salt such as nickel sulfate, nickel chloride, or nickel carbonate.
[0095] As the complexing agent, for example, citric acid or a salt thereof, pyrophosphoric acid or a salt thereof, 1-hydroxyethane-1,1-bisphosphonic acid, etc. can be used.
[0096] Examples of citrate salts include trisodium citrate, disodium hydrogen citrate, sodium dihydrogen citrate, tripotassium citrate, dipotassium hydrogen citrate, potassium dihydrogen citrate, trilithium citrate, dilithium hydrogen citrate, lithium dihydrogen citrate, triammonium citrate, diammonium hydrogen citrate, and ammonium dihydrogen citrate.
[0097] Furthermore, ammonium ions have the effect of increasing current efficiency, and the plating solution used may contain either an ammonium salt or ammonia.
[0098] The Ni concentration in the plating solution used in the electroplating step is preferably 1 g / L or more and 30 g / L or less, and more preferably 3 g / L or more and 10 g / L or less.
[0099] The W concentration in the plating solution used in the electroplating step is preferably 20 g / L or more and 200 g / L or less, and more preferably 30 g / L or more and 100 g / L or less.
[0100] The pH (pH at 25° C.) of the plating solution used in the electroplating step is not particularly limited, but is preferably from 5.0 to 7.0, and more preferably from 5.5 to 6.8.
[0101] The cathode current density in the electroplating process is 3A / dm 2 More than 30A / dm 2 It is preferable that it is less than 7A / dm 2 More than 15A / dm 2 More preferably, it is:
[0102] The treatment temperature in the electroplating step is not particularly limited, but is preferably 25°C or higher and 80°C or lower, and more preferably 35°C or higher and 65°C or lower.
[0103] The processing conditions in the electroplating step (eg, processing temperature, etc.) may be changed during the electroless plating step.
[0104] The treatment time for the electroplating step is not particularly limited, but is preferably, for example, from 1 minute to 240 minutes, more preferably from 3 minutes to 120 minutes, and even more preferably from 5 minutes to 30 minutes.
[0105] This can improve the reliability of the finally obtained high hardness and wear resistant member 100. Also, the productivity of the high hardness and wear resistant member 100 can be improved.
[0106] It is preferable that the Ni--W alloy plating layer 2B' formed in the electroplating step contains W in a solid solution amount equal to or greater than the solid solubility limit.
[0107] This allows the W single-phase crystals to be more suitably precipitated in the W single-phase crystal formation step, and the effects described in detail below are more significantly exhibited.
[0108] The Ni--W alloy plating layer 2B' in which W is dissolved to a degree equal to or greater than the solubility limit can be suitably formed by carrying out the electroplating step under the above-mentioned preferable conditions.
[0109] The thickness of the Ni-W alloy plating layer 2B' formed in the electroplating process is not particularly limited, but is preferably 1.0 μm or more and 10 μm or less, more preferably 1.4 μm or more and 5.0 μm or less, and even more preferably 2.5 μm or more and 3.0 μm or less.
[0110] This makes it possible to suitably adjust the thickness of the coating 2, the thickness of the parent phase 21, and the thickness of the hard layer 22 in the finally obtained high hardness and wear-resistant component 100 so as to satisfy the above-mentioned conditions.
[0111] [2-4] W single-phase crystal formation process In the W single-phase crystal formation step, the base material 1 on which the electroless Ni-P plating layer 2A' and the Ni-W alloy plating layer 2B' are formed is subjected to a heat treatment in a reducing atmosphere to form a composite layer 2' containing W single-phase crystals and a solid solution containing Ni and Fe (1d). More specifically, by performing a heat treatment in a reducing atmosphere, the solid solution of Ni and Fe progresses, and the amount of solid-solution W decreases, causing W to precipitate as single-phase particles. In this way, by precipitating the W single-phase particles in this step, the WC particles generated in the subsequent carburization treatment step are effectively prevented from becoming coarse. Note that the Fe contained in the solid solution is usually diffused from the base material 1.
[0112] The W single-phase crystals formed in the W single-phase crystal formation process will become mainly WC crystal grains in the subsequent carburization process.
[0113] The atmosphere in which the W single phase crystal formation step is carried out may be any reducing atmosphere, and specifically, for example, an atmosphere containing hydrogen gas may be mentioned.
[0114] Examples of the hydrogen gas-containing atmosphere include hydrogen gas itself, and a mixed gas of hydrogen gas and an inert gas such as nitrogen gas or argon gas.
[0115] In particular, the atmosphere in which the W single phase crystal formation step is carried out is preferably a mixed gas of hydrogen gas and argon gas.
[0116] The pressure of hydrogen gas in the atmosphere in which the W single phase crystal formation process is carried out (the partial pressure of hydrogen gas in the case of a mixed gas of hydrogen gas and other components) is preferably 1 kPa or more and 100 kPa or less, more preferably 3 kPa or more and 20 kPa or less, and even more preferably 7 kPa or more and 10 kPa or less.
[0117] The pressure of the atmosphere during the W single phase crystal formation step is preferably 50 kPa or more and 500 kPa or less, more preferably 100 kPa or more and 350 kPa or less, and even more preferably 140 kPa or more and 200 kPa or less.
[0118] The treatment temperature of the heat treatment in a reducing atmosphere in the W single phase crystal formation step is preferably 500°C or higher and 1000°C or lower, more preferably 550°C or higher and 800°C or lower, and even more preferably 650°C or higher and 700°C or lower.
[0119] This allows the solid solution of Ni and Fe to proceed more efficiently, and allows single-phase W particles to precipitate more efficiently, making it possible to more efficiently form a composite layer 2' containing single-phase W crystals and a solid solution containing Ni and Fe, thereby improving the productivity of the high-hardness, wear-resistant member 100 and improving the reliability of the finally obtained high-hardness, wear-resistant member 100.
[0120] The treatment conditions in the W single phase crystal formation step (for example, the composition of the atmosphere, the pressure, the treatment temperature, etc.) may be changed during the W single phase crystal formation step.
[0121] The heating rate in the W single phase crystal formation process (e.g., heating rate from 20°C to 500°C) is preferably 50°C / min to 250°C / min, more preferably 80°C / min to 220°C / min, and even more preferably 120°C / min to 200°C / min.
[0122] This allows the solid solution of Ni and Fe to proceed more efficiently, and allows single-phase W particles to precipitate more efficiently, making it possible to more efficiently form a composite layer 2' containing single-phase W crystals and a solid solution containing Ni and Fe, thereby improving the productivity of the high-hardness, wear-resistant member 100 and improving the reliability of the finally obtained high-hardness, wear-resistant member 100.
[0123] The treatment time of the heat treatment in a reducing atmosphere in the W single phase crystal formation process (e.g., treatment time at 500°C or higher) is preferably 10 minutes or more and 180 minutes or less, more preferably 20 minutes or more and 90 minutes or less, and even more preferably 30 minutes or more and 60 minutes or less.
[0124] This can improve the reliability of the finally obtained high hardness and wear resistant member 100. Also, the productivity of the high hardness and wear resistant member 100 can be improved.
[0125] [2-5] Carburizing process In the carburizing process, the composite layer 2' is subjected to gas carburizing treatment to form WC crystal grains (1e).
[0126] As a result, the composite layer 2' becomes the coating 2 having the matrix 21 and the hard layer 22, and a high-hardness, wear-resistant member 100 is obtained.
[0127] Furthermore, by subjecting the composite layer 2' formed as described above to a carburizing treatment, the parent phase 21 can be suitably formed as one composed of a solid solution containing W in addition to Ni and Fe.
[0128] The carburizing step is carried out by subjecting the composite layer 2' to a heat treatment in an atmosphere containing a carburizing gas.
[0129] Examples of the carburizing gas include hydrocarbons such as propane, propylene, ethylene, and acetylene, and CO. One or more selected from these gases may be used in combination. In addition, RX gas may be used.
[0130] The temperature of the heat treatment in the carburizing step is preferably 650°C or higher and 1000°C or lower, more preferably 750°C or higher and 950°C or lower, and even more preferably 800°C or higher and 900°C or lower.
[0131] This allows the carburizing process to be carried out more efficiently, improving the productivity of the high hardness, wear-resistant member 100 and improving the reliability of the final high hardness, wear-resistant member 100.
[0132] The treatment conditions in the carburizing process (eg, the composition of the carburizing gas, the pressure, the treatment temperature, etc.) may be changed during the carburizing process.
[0133] The heating rate in the carburizing process (e.g., the heating rate from 200°C to 650°C) is preferably 50°C / min to 250°C / min, more preferably 80°C / min to 220°C / min, and even more preferably 120°C / min to 200°C / min.
[0134] This allows the carburizing process to be carried out more efficiently, improving the productivity of the high hardness, wear-resistant member 100 and improving the reliability of the final high hardness, wear-resistant member 100.
[0135] The treatment time for the carburizing treatment (for example, treatment time at 650° C. or higher) is preferably 3 minutes or more and 180 minutes or less, more preferably 5 minutes or more and 120 minutes or less, and even more preferably 10 minutes or more and 60 minutes or less.
[0136] This can improve the reliability of the finally obtained high hardness and wear resistant member 100. Also, the productivity of the high hardness and wear resistant member 100 can be improved.
[0137] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to these.
[0138] For example, the method for producing a high hardness, wear-resistant member of the present invention may include steps other than the steps described above (for example, a pre-treatment step, an intermediate treatment step, a post-treatment step, etc.).
[0139] More specifically, for example, the manufacturing method of the high hardness and wear-resistant member of the present invention may include a cleaning step for cleaning the surface as at least one of the pre-treatment step, intermediate treatment step, and post-treatment step. The manufacturing method of the high hardness and wear-resistant member of the present invention may also include a film thickness adjustment step for adjusting the thickness of the layer formed in the previous step by polishing or the like as an intermediate step. The manufacturing method of the high hardness and wear-resistant member of the present invention may also include a film formation step for forming a film other than the above-mentioned coating after the carburizing step.
[0140] Furthermore, the method for producing a high-hardness, wear-resistant member of the present invention can also be applied to, for example, the repair and modification of a high-hardness, wear-resistant member.
[0141] For example, by preparing a member having a different configuration from the high hardness and wear-resistant member of the present invention as the above-mentioned substrate, for example, various tools such as cutting tools, various rolls such as metal molds, rolling rolls, piston rings, cylinders, bearings, various sliding parts such as bearings, various valves and pump parts, etc., which require high hardness and excellent wear resistance, and applying the manufacturing method of the present invention to the member (substrate member), a high hardness and wear-resistant member for repair and remodeling can be obtained. When such a member is used as the substrate, a process such as removing a part of the substrate may be carried out prior to the above-mentioned electroless plating process.
[0142] Furthermore, for example, the high hardness and wear-resistant member of the present invention may be manufactured by a method other than those described above, as long as it has a substrate and a coating, and the coating has a matrix composed of a material containing a solid solution containing Ni and Fe, and a hard layer composed of a material containing WC crystal particles and supported by the matrix.
[0143] In the above-described embodiment, the coating is typically composed of a matrix provided on the substrate side and a hard layer provided on the surface side of the harder, wear-resistant member than the matrix. However, the coating may have any structure as long as it has a matrix and a hard layer, and may have, for example, regions in which the matrix and the hard layer are mixed together. EXAMPLES
[0144] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited thereto. Note that the treatments and measurements not specifically indicated as temperature conditions were carried out at 25°C.
[0145] [3] Manufacturing of high-hardness, wear-resistant parts Example 1 First, carbon steel S45C was prepared as the base material, and the surface was given a mirror finish.
[0146] Next, the mirror-finished substrate was subjected to electroless plating using a plating solution containing NiSO4·6H2O: 0.09 mol / L, NaPH2O2·H2O: 0.28 mol / L, CH3COONa: 0.12 mol / L, citric acid: 0.05 mol / L, Ni concentration: 5.3 g / L, and pH: 3.7 at 25°C, to form an electroless Ni-P plating layer (electroless plating process).
[0147] The treatment temperature in the electroless plating step was 85° C., and the treatment time in the electroless plating step was 30 minutes.
[0148] The electroless Ni-P plating layer formed in the electroless plating step had a thickness of 1.0 μm.
[0149] Next, a Ni-W alloy plating layer was formed by electroplating on the electroless Ni-P plating layer formed as described above (electroplating step).
[0150] The plating solution used for the electroplating process was NiSO4·6H2O: 0.06 mol / L, Na2WO4·2H2O: 0.26 mol / L, citric acid: 0.05 mol / L, 14.8 N ammonia water: 8 mL, and pH: 6.2 at 25°C.
[0151] In addition, the cathode current density in the electroplating process is 10A / dm 2The treatment temperature in the electroplating process was 50° C., and the treatment time in the electroplating process was 10 minutes. The thickness of the Ni-W alloy plating layer formed by the electroplating process was 2.0 μm.
[0152] Next, the substrate on which the electroless Ni-P plating layer and Ni-W alloy plating layer were formed was subjected to a heat treatment in a mixed gas atmosphere (150 kPa) of hydrogen gas and argon gas, with a hydrogen gas partial pressure of 7.5 kPa and an argon gas partial pressure of 142.5 kPa, at a treatment temperature of 650°C for a treatment time (treatment time at 500°C or higher): 60 minutes, to form a composite layer containing W single-phase crystals and a solid solution containing Ni and Fe (W single-phase crystal formation process). The temperature rise rate from 200°C to 500°C was 160°C / min. The Fe contained in the solid solution constituting the composite layer was diffused from the substrate.
[0153] Next, the composite layer obtained as described above was subjected to gas carburization treatment using a mixed gas of acetylene gas and argon gas to form WC crystal particles, form a hard layer, and form a matrix composed of a solid solution containing Ni, Fe, and W, forming a coating having a matrix and a hard layer, thereby obtaining a high-hardness, wear-resistant member (carburization treatment process). A mixed gas (320 kPa) of acetylene gas (4.8 kPa) and argon gas (315.2 kPa) was used for the gas carburization treatment.
[0154] The heat treatment temperature in the carburizing process was 900°C, the carburizing process time (treatment time at 650°C or higher) was 10 minutes, and the temperature rise rate in the carburizing process (rate of temperature rise from 200°C to 650°C) was 160°C / minute.
[0155] The hard layer thus formed contained rod-shaped WC crystal grains, each of which had a minor axis length of 0.30 μm and a major axis length of 2.2 μm.
[0156] (Examples 2 to 4) A high hardness, wear-resistant member was produced in the same manner as in Example 1, except that the processing conditions in each step were changed as shown in Table 1 so that the structure of the high hardness, wear-resistant member was as shown in Table 2.
[0157] (Comparative Examples 1 and 2) A high hardness and wear resistant member was manufactured in the same manner as in Example 1, except that the W single phase crystal formation process was omitted and the treatment time of the electroplating process and the treatment conditions of the carburizing process were changed as shown in Table 1 so that the configuration of the high hardness and wear resistant member was as shown in Table 2.
[0158] Comparative Example 3 A high hardness and wear resistant member was produced in the same manner as in Example 3, except that the carburizing treatment step was omitted.
[0159] For each of the examples and comparative examples, the manufacturing conditions for the high hardness and wear resistant members are shown in Table 1, and the configurations of the high hardness and wear resistant members are shown in Table 2.
[0160] [Table 1]
[0161] [Table 2]
[0162] At the end of the W single-phase crystal formation process and at the end of the carburizing process for each of the examples and comparative examples, analysis was performed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). For X-ray diffraction, an X-ray diffractometer Rint2100 manufactured by Rigaku Corporation was used, and for taking surface SEM photographs and cross-sectional SEM photographs, a JSM-5310LVB Scanning Electron Microscope and a JCM-6000 NeoScope manufactured by JEOL Ltd. were used.
[0163] FIG. 3 shows X-ray diffraction (XRD) patterns at the end of the W single-phase crystal formation process and at the end of the carburization process for Examples 1 and 2, FIG. 4 shows X-ray diffraction (XRD) patterns at the end of the carburization process for Examples 3 and 4, FIG. 5 shows X-ray diffraction (XRD) patterns at the end of the carburization process for Comparative Examples 1 and 2, FIG. 6 shows surface SEM (scanning electron microscope) photographs for the high hardness and wear resistant members of Examples 1 and 2, FIG. 7 shows surface SEM (scanning electron microscope) photographs for the high hardness and wear resistant members of Comparative Examples 1 and 2, and FIG. 8 shows the results of cross-sectional energy dispersive X-ray analysis (EDS) at the end of the W single-phase crystal formation process for Example 3. The results of surface energy dispersive X-ray analysis (EDS) at the end of the carburizing treatment process for Example 3 are shown in FIG. 9, the results of surface electron backscatter diffraction (EBSD) at the end of the carburizing treatment process for Example 3 are shown in FIG. 10, the results of cross-sectional energy dispersive X-ray analysis (EDS) at the end of the carburizing treatment process for Example 3 are shown in FIG. 11, the results of surface energy dispersive X-ray analysis (EDS) at the end of the carburizing treatment process for Example 4 are shown in FIG. 12, the results of surface EDS / EBSD at the end of the carburizing treatment process for Example 4 are shown in FIG. 13, and the results of cross-sectional energy dispersive X-ray analysis (EDS) at the end of the carburizing treatment process for Example 4 are shown in FIG. 14.
[0164] As is clear from Figures 3 and 4, in the present invention, at the end of the W single-phase crystal formation process, a peak of precipitated W is observed, whereas at the end of the carburizing process, the peak of W disappears and a strong peak of WC appears. In contrast, in Comparative Examples 1 and 2, as is clear from Figure 5, a peak of W2C, which is considered to be disadvantageous in improving wear resistance, was also confirmed along with the peak of WC. Also, from Figure 6, in the high hardness and wear-resistant member of the present invention, WC crystals were confirmed, whereas W2C crystals were not confirmed. In particular, in Example 1, in which the processing time of the carburizing process was relatively short, relatively small rod-shaped WC crystal particles were mainly present, whereas in Example 2, in which the processing time of the carburizing process was relatively long, the growth of rod-shaped WC crystal particles was confirmed. In contrast, from Figure 7, in Comparative Examples 1 and 2, many W2C particles as fine particles were confirmed along with needle-shaped WC particles. 8 shows that a member having a homogeneous Ni-W alloy coating, an electroless Ni-P plating film as an undercoat, and a base material mainly composed of Fe is obtained by going through the steps up to the W single-phase crystal formation step. 9 to 11 show that in the high-hardness, wear-resistant member of Example 3 obtained by a comparatively short carburization treatment, fine, elongated WC crystal particles (particularly WC crystal particles with a size of about 1 μm) are spread on the surface, Ni and Fe are mutually diffused, and P contained in the undercoat has migrated to the surface area. 12 to 14, it can be seen that in the high-hardness, wear-resistant part of Example 4, which was obtained by performing heat treatment (W single-phase crystal formation process) for a longer time in a reducing atmosphere than in Example 3, fine columnar WC crystal particles with triangular cross sections (particularly WC crystal particles having a size of about 3 μm or less) are spread over the surface, P contained in the base has migrated to the area near the surface (particularly P is unevenly distributed in Ni and Fe), and a solid solution of Ni and Fe has been formed.
[0165] [4] Evaluation [4-1] Hardness evaluation The surfaces on which the coatings were formed of the high-hardness, wear-resistant members obtained in the above-mentioned Examples and Comparative Examples were subjected to measurements in accordance with JIS Z 2244 using a microhardness tester (Fisher Instruments, Picodentor HM500) to determine the Vickers hardness.
[0166] [4-2] Evaluation of wear resistance For the surfaces on which the coatings of the high hardness and wear-resistant members obtained in each of the Examples and Comparative Examples were provided, a ball-on-disk friction and wear test was carried out using a ball-on-disk friction and wear tester (manufactured by CSM Instruments, Tribometer) according to a method conforming to ISO 18535, and the specific wear rate was determined. These results are summarized in Table 3.
[0167] [Table 3]
[0168] As is clear from Table 3, in each of the Examples, a high-hardness, wear-resistant member that achieved both hardness and wear resistance was obtained. In contrast, in each of the Comparative Examples, satisfactory results were not obtained.
[0169] In addition, the thickness of the electroless Ni-P plating layer formed in the electroless plating step is within the range of 0.01 μm to 10 μm, the thickness of the Ni-W alloy plating layer formed in the electroplating step is within the range of 1.0 μm to 10 μm, the heat treatment temperature in the W single phase crystal formation step is within the range of 500° C. to 1000° C., the heat treatment time in the W single phase crystal formation step is within the range of 10 minutes to 180 minutes, the heat treatment temperature in the carburizing treatment step is within the range of 650° C. to 1000° C., and the heat treatment temperature (carburizing time) in the carburizing treatment step is within the range of 3 minutes to 180 minutes. High hardness and wear-resistant members were manufactured in the same manner as in the above-mentioned Examples, except that the thickness of the parent phase of the high hardness and wear-resistant members was changed to within the range of 1.0 μm or more and 2.5 μm or less, the thickness of the hard layer was changed to 0.5 μm or more, the minor axis length of the WC crystal grains was changed to within the range of 0.10 μm or more and 1.4 μm or less, the major axis length was changed to within the range of 1.0 μm or more and 4.0 μm or less, and the thickness of the coating was changed to within the range of 1.5 μm or more and 5.0 μm or less. These high hardness and wear-resistant members were evaluated in the same manner as above, and it was confirmed that the same effects as above could be obtained. [Industrial Applicability]
[0170] The high-hardness, wear-resistant member of the present invention has a substrate and a coating, and the coating has a matrix made of a material containing a solid solution of Ni and Fe, and a hard layer made of a material containing WC crystal particles and supported by the matrix. This makes it possible to provide a high-hardness, wear-resistant member that has high hardness and excellent wear resistance, as well as excellent adhesion between the substrate and the hard coating.
[0171] The method for producing a high-hardness, wear-resistant member of the present invention includes the steps of electroless plating of a substrate made of a material containing Fe by electroless Ni-P plating to form an electroless Ni-P plating layer, electroplating of a Ni-W alloy plating layer on the electroless Ni-P plating layer by electroplating, forming a W single-phase crystallization layer by heat treatment in a reducing atmosphere to form a composite layer containing W single-phase crystals and a solid solution containing Ni and Fe, and forming WC crystal particles by gas carburization of the composite layer. This makes it possible to provide a method for producing a high-hardness, wear-resistant member that has high hardness and excellent wear resistance, and also has excellent adhesion between the substrate and the hard coating.
[0172] Therefore, the high hardness and wear-resistant member and the method for producing the high hardness and wear-resistant member of the present invention have industrial applicability. [Explanation of symbols]
[0173] 100…High hardness and wear-resistant material 1...Base material 2...Coating 21…Mother phase 22…Hard layer 2A': Electroless Ni-P plating layer 2B': Ni-W alloy plating layer 2'…Composite layer
Claims
1. A high-hardness, wear-resistant member having a substrate and a coating, the coating has a matrix made of a material including a solid solution containing Ni and Fe, and a hard layer made of a material including WC crystal grains and supported by the matrix, The mother phase is provided in a layer shape between the substrate and the hard layer, A high-hardness, wear-resistant member, wherein the WC crystal grains have a minor axis length of 0.10 μm or more and 1.4 μm or less and a major axis length of 1.0 μm or more and 4.0 μm or less.
2. 2. The high-hardness, wear-resistant member according to claim 1, wherein the hard layer has a thickness of 0.5 μm or more.
3. 3. The high-hardness, wear-resistant member according to claim 1, wherein the substrate is made of a steel material.
4. 4. The high-hardness, wear-resistant member according to claim 3, wherein the substrate is made of carbon steel.
5. 5. The high-hardness, wear-resistant member according to claim 1, wherein the coating has a thickness of 1.5 μm or more and 5.0 μm or less.
6. 6. The high-hardness, wear-resistant member according to claim 1, wherein the hard layer contains rod-like WC crystal grains.
7. an electroless plating process of applying electroless Ni-P plating to a base material made of a material containing Fe to form an electroless Ni-P plating layer; an electroplating step of forming a Ni—W alloy plating layer on the electroless Ni—P plating layer by electroplating; a W single-phase crystal forming step of forming a composite layer containing W single-phase crystals and a solid solution containing Ni and Fe by performing a heat treatment in a reducing atmosphere; and a carburizing step of forming WC crystal grains by subjecting the composite layer to a gas carburizing treatment.
8. 8. The method for producing a high-hardness, wear-resistant member according to claim 7, wherein the electroless Ni-P plating layer formed in the electroless plating step has a thickness of 0.01 μm or more and 10 μm or less.
9. 9. The method for producing a high-hardness, wear-resistant member according to claim 7, wherein the thickness of the Ni--W alloy plating layer formed in the electroplating step is 1.0 μm or more and 10 μm or less.
10. 10. The method for producing a high hardness and wear resistant member according to claim 7, wherein the W single phase crystal formation step is carried out by carrying out a heat treatment at 500° C. to 1000° C. in a reducing atmosphere.
11. 11. The method for producing a high hardness and wear resistant member according to claim 7, wherein the W single phase crystal formation step is carried out by carrying out a heat treatment in a reducing atmosphere for 10 minutes or more and 180 minutes or less.
12. 12. The method for producing a high hardness and wear resistant member according to claim 7, wherein the carburizing step is carried out by carrying out a heat treatment at 650° C. to 1000° C. in an atmosphere containing a carburizing gas.
13. 13. The method for producing a high-hardness, wear-resistant member according to claim 7, wherein the carburizing step is carried out by carrying out a heat treatment for 3 minutes or more and 180 minutes or less in an atmosphere containing a carburizing gas.
Citation Information
Patent Citations
Method for coating product sensitive to high temperature with hard layer and coated product
JP1989165755A
High-speed tool steel and its production method
JP2004307963A
Cold tool steel having reduced alloy addition amount
JP2014145100A
Composite member and cutting tool composed of the same
JP2018016875A
